2015 Equilibrium Committee Amendment to the 1995 AAO-HNS Guidelines for the Definition of Ménière's Disease - Goebel, Joel A (Otolaryngology-head and neck surgery, 2016)
Ménière's disease is a disorder of the inner ear that causes attacks of vertigo and hearing loss, tinnitus, aural fullness in the involved ear. Over the past 4 decades, the Equilibrium Committee of the AAO-HNS has issued guidelines for diagnostic criteria, with the latest version being published in 1995. These criteria were reviewed in 2015 by the Equilibrium Committee, and revisions were approved at the recent meeting of the committee at the 2015 AAO-HNSF Annual Meeting. The following commentary outlines the amended and approved criteria.